Analysis of Hydroxy Fatty Acids from the Pollen of Brassica campestris L. var. oleifera DC. by UPLC-MS/MS. (10th October 2012) - Yang, Nian-Yun; Yang, Yi-Fang; Li, Kun
Abstract : Ultraperformance liquid chromatography coupled with negative electrospray tandem mass spectrometry (UPLC-ESI-MS/MS) was used to determine 7 hydroxy fatty acids in the pollen of Brassica campestris L. var. oleifera DC. All the investigated hydroxy fatty acids showed strong deprotonated molecular ions [M–H] −, which underwent two major fragment pathways of the allyl scission and the β -fission of the alcoholic hydroxyl group. By comparison of their molecular ions and abundant fragment ions with those of reference compounds, they were tentatively assigned as 15, 16-dihydroxy-9Z, 12Z-octadecadienoic acid (1 ), 10, 11, 12-trihydroxy-(7Z, 14Z)-heptadecadienoic acid (2 ), 7, 15, 16-trihydroxy-9Z, 12Z-octadecadienoic acid (3 ), 15, 16-dihydroxy-9Z, 12Z-octadecadienoic acid (4 ), 15-hydroxy-6Z, 9Z, 12Z-octadecatrienoic acid (5 ), 15-hydroxy-9Z, 12Z- octadecadienoic acid (6 ), and 15-hydroxy-12Z-octadecaenoic acid (7 ), respectively. Compounds 3, 5, and 7 are reported for the first time.